2008
DOI: 10.1177/0959353508096180
|View full text |Cite
|
Sign up to set email alerts
|

Putting the New View Classification Scheme to an Empirical Test

Abstract: Dissatisfaction with prevailing 'biomedical' approaches to the construction and classification of female sexual problems led to the development of A New View of Women's Sexual Problems. In order to test the utility of the New View classification scheme, its correspondence was assessed by questionnaire with 49 women's own accounts of sexual difficulty. Results demonstrated significant correspondence in several ways. Furthermore, sexual difficulties were attributed to relational (65%) and contextual/external (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Previous research has indicated that relationship variables are particularly important to women's sexual functioning and satisfaction (Basson, 2005;Byers, 2001;Dennerstein, Lehert, Burger, & Guthrie, 2005;Ellison, 2001;Nicholls, 2008;Prins et al, 1993). The pattern of results from the current study, indicating that women were more likely to engage in infidelity when they were dissatisfied in their relationship or felt incompatible with their partner in terms of sexual values, suggests that the interconnected nature of sexual and relationship factors may be one of the reasons women engage in infidelity.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…Previous research has indicated that relationship variables are particularly important to women's sexual functioning and satisfaction (Basson, 2005;Byers, 2001;Dennerstein, Lehert, Burger, & Guthrie, 2005;Ellison, 2001;Nicholls, 2008;Prins et al, 1993). The pattern of results from the current study, indicating that women were more likely to engage in infidelity when they were dissatisfied in their relationship or felt incompatible with their partner in terms of sexual values, suggests that the interconnected nature of sexual and relationship factors may be one of the reasons women engage in infidelity.…”
Section: Discussionmentioning
confidence: 40%
“…The pattern of results from the current study, indicating that women were more likely to engage in infidelity when they were dissatisfied in their relationship or felt incompatible with their partner in terms of sexual values, suggests that the interconnected nature of sexual and relationship factors may be one of the reasons women engage in infidelity. Evidence from a number ofstudies suggeststhatwomen aremorelikely than men to link sexual and relationship satisfaction (Basson, 2005;Ellison, 2001;McCabe, 1999;McCabe & Cobain, 1998;Nicholls, 2008). For example, McCabe and Cobain (1998) found that women who experienced sexual problems allowed these problems to impact their relationship satisfaction but sexual problems and relationship satisfaction were relatively independent for men.…”
Section: Discussionmentioning
confidence: 92%
“…Unlike the DSM, the New View classification system is not based on symptom criteria, but is instead organized around four possible categories of causes: sociocultural, political, or economic factors; partner and relationship factors; psychological factors; and medical factors. Nicholls (2008) examined the degree to which women's accounts of their sexual difficulties accorded with the New View framework. Although this was a small study, involving only 49 women, the findings did support the utility of the New View perspective.…”
Section: Critiques Of Dsm-iv-tr Criteria For Female Orgasmic Disordermentioning
confidence: 99%
“…The advantage of this model is that it avoids defining any one particular pattern of experience, focuses on causation which would guide treatment, and is sensitive to the important influence of sociocultural, political, and economic factors that influence sexual function. In a recent study that explored the extent to which the New View framework corresponded with women's accounts of their sexual difficulties, an open-ended questionnaire was administered to 49 British women who were asked to describe their sexual difficulties in their own words (Nicholls, 2008). Using language equivalents and thematic content, women's accounts of their difficulties were divided into 108 distinct issues.…”
Section: Other Classification Systemsmentioning
confidence: 99%